Railing Rhymes Revisited: Libels, Scandals, and Early Stuart Politics - Bellany, Alastair James (History compass, 2007)
This article surveys and assesses recent interdisciplinary scholarship on early Stuart verse libels - scandalous, defamatory poems surreptitiously circulating criticism of courtiers, councilors, and royal policies. It situates this scholarship within revisionist and post-revisionist historians’ debates on the nature of early Stuart politics and the causes of the English Revolution, and within the cultural turn in early modern studies and in the discipline of history at large. The article then surveys what scholars have argued about the libel as a form of political media operating within an early modern literary underground and an emerging public sphere, and as a form of political expression which articulated serious critique through allegations of sexual and other forms of personal corruption. It concludes with suggestions for future research.